Cognitive factors that predict on-sight and red-point performance in sport climbing at youth level - Vasile, Antonia Ioana; Stănescu, Monica; Pelin, Florin; Bejan, Roxana (Frontiers in Psychology, 2022)
Introduction The ascent of a route can be defined as being climbed on-sight or red-point. Climbing performance is measured by the grade of the personal best route that the athlete has ever climbed. Methodology The study examined 17 youth climbers (10 male and 7 female). The inclusion criteria were age (less than 20 years), a minimum of three sessions per week, a minimum 7a climbing grade and participation in national or international competitions. We used the Cognitrom battery and applied tests measuring spatial orientation and reactivity. Results Climbing experience explained 42.7% of the variance of on-sight performance, and 49.5% of the variance of red-point performance. Image generation has a negative on both on-sight and red-point performance, lowering the prediction with 0.5% for on-sight climbing and with 1.5% for red-point climbing. Discussion Experience can predict climbing performance with a better prediction for red-point performance than on-sight with almost 7%. A high level of image generation ability can lead to viewing more approaches for passing the crux, but in a moment of physical and mental breakdown, can lead to failure. Red-pointing is less demanding than on-sight from physiological and psychologycal points of view. On-sight climbing requires greater levels of cognitive skills, such as route intepretation strategies, spatial orientation, motric memory, problem-solving skills, but also greater levels of psychological skills such as stress management, risk management, coping anxiety.